Equity carve-outs, dual directors, and internal labor markets - Pengda Fan (International Journal of Financial Studies, 2022)
Given the prevalence of dual directors who serve simultaneously on the parent as well as the subsidiary board, it is important to examine their functions, a topic largely ignored in the existing literature. Exploring the functions of dual directors highlights equity carve-out objectives other than strategic refocusing. To examine our hypothesis, we first conducted an event study to examine stock market reaction to carve-out decisions. In addition, we compared subsidiaries' performance after carve-outs between firms with dual directors and their matching firms based on the propensity score. We find evidence that the Japanese stock market reacts positively to the presence of dual directors who hold CEO positions in carve-out subsidiaries, especially when they are relatively young. Additionally, we find that carve-out subsidiaries led by young dual directors tend to outperform their matched counterparts in the long run. In contrast, when dual directors do not hold the CEO position, we find no evidence of the stock market reacting positively to them. The results of this study suggest that young CEOs appointed from the internal labor markets care more about long-term reputation, and can enhance shareholder wealth of both parent and subsidiary firms.
Keywords: 330; dual directors; equity carve-out; internal labor markets